Guidelines for reporting molecular typing data through EFSA's Data Collection Framework. Issue 1 (25th January 2019) - ,; Delfino, Alessandro; Pasinato, Luca; Rizzi, Valentina; Stoicescu, Anca‐Violeta
Abstract : The European Food Safety Authority (EFSA) received the mandate from the European Commission (EC), in accordance with Article 31 of Regulation (EC) No. 178/2002, to collect data on the molecular testing of food‐borne pathogens such as Salmonella, Listeria monocytogenes and Shiga toxin‐producing Escherichia coli (STEC) from food, feed, animals and the related environment, to contribute to the epidemiological investigations of food‐borne outbreaks and to the identification of emerging health threats. EFSA is asked to collaborate with the European Centre for Disease Prevention and Control (ECDC), the Member States (MS) and European Union Reference Laboratories (EURL) for the collection of molecular typing data on isolates from food and food‐producing animals. This technical report is aimed to guide the EU MS in molecular typing data submission through the Data Collection Framework (DCF) using eXtensible Markup Language (XML), based on the Standard Sample Description 2.0 (SSD2) data model.